STAGES OF IMPLEMENTATION OF AN INTEGRATED MANAGEMENT SYSTEM FOR HEALTH RESORT COMPANIES - Subota, M.V.; Dubina , M.P. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The aim is to develop theoretical approaches and practical recommendations for identifying and guiding a detailed description of the stages of implementation of an integrated management system for sanatorium-resort enterprises in the context of their sustainable development. On the basis of the set of scientific methods and approaches used in the study, including structuring and generalization, systematization, synthesis and argumentation, it was possible to ensure the conceptual and structural unity of the study, to determine the stages of implementation of an integrated management system for sanatorium-resort enterprises in the context of their sustainable development. As a result of the study, a system and a sequence of interrelated stages of implementation of an integrated management system for sanatorium-resort enterprises in the context of their sustainable development are proposed. It has been determined that the introduction of the principles of the concept of sustainable development into the management system has a positive effect on increasing the internal motivation and responsibility of employees, on the social component of the safety of health resort enterprises. Highlighted the implementation of the service quality management system as an important component of the integrated management system. The environmental management system is identified as an important tool for identifying and reducing ineffective activities. As a result of the study, a system and a sequence of interrelated stages of the implementation of an integrated management system have been proposed, including: determination of the circle of interested persons (individuals or legal entities) who can be significantly affected by the economic activities of sanatorium-resort institutions; critical analysis of legal compliance; formation of the quality management system policy; support and involvement of the top management of sanatorium-resort institutions; awareness of employees of health resort institutions; determination of persons responsible for the implementation of the system; VSM-mapping of the current state; definition of goals and objectives; determination of performance indicators; contextualization of indicators of sustainable development of sanatorium and resort enterprises; formation of a VSM-map of the future state of development of a sanatorium-resort institution; identifying opportunities for improvement.